Bullying-Free Education: A Study of Governance in Madrasah Tsanawiyah after the Regulation Number 82 of 2015 - Halid, Ahmad (Journal of Asian Islamic Educational Management (JAIEM), 2023)
Bullying-free education is an ideal that must be realized in every educational unit; through Permindkbud No. 82 of 2015 guarantees that students can study quietly and peacefully at school without any violence from anyone. The problem of this research is how to plan and implement bullying-free education: Governance Study at MTs Miftahul Ulum Renes Wirowongso Ajung Jember after the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 82 of 2015. The aim is to analyze, find out and reconstruct bullying-free educational planning at MTs Miftahul Ulum. Bully-free planning is carried out with four plans, namely (1) organizing bullying, (2) teacher council meetings, (3) student parents meetings, and p (4) learning planning (RPP), while the implementation includes (1) Teachers teaching while advising about free bullying, (2) Socialization of bullying violence, (3) Sanctions for bullying perpetrators, (4) Anti-bullying curriculum, (5) Guidance and Counseling, (6) Mediation to overcome bullying violence.